Overview of infestation status and management of the rice leaffolder, Cnaphalocrocis medinalis (Guenée) (Lepidoptera: Pyralidae), in Malaysian paddy areas - Nor Aida Shafina Mustapar; Nur Athiqah Md Yusof; Salmah Mohamed; Marina Roseli (Universitas Lampung, 2026)
The rice leaffolder, Cnaphalocrocis medinalis (Guenée) (Lepidoptera: Pyralidae), is a major foliar pest of rice (Oryza sativa L.) across Asia, including Malaysia, where recent outbreaks have re-established it as a significant constraint to rice productivity. This review synthesizes current knowledge on its biology, life cycle, feeding behavior, and ecological interactions within Malaysian rice agroecosystems. Available evidence indicates that pest outbreaks are closely associated with environmental factors, particularly high humidity and dense crop canopies, while natural enemies—including parasitoids and predators—play a critical role in regulating field populations. Habitat management practices, such as the introduction of flowering plants along rice bunds, may enhance natural enemy activity and contribute to the suppression of rice leaffolder populations. In addition, augmentative biological control using Trichogramma spp. represents a promising strategy for early-stage suppression of the pest. Integrating these ecological and biological approaches within an Integrated Pest Management (IPM) framework offers a viable pathway to reduce reliance on chemical inputs while improving system resilience. This review also identifies key research gaps and provides directions for developing locally adapted, sustainable management strategies for C. medinalis in Malaysia.